Transformation of tobacco (Nicotiana tabacum l.) with the oil palm Cinnamyl alcohol dehydrogenase 2 gene - Mohd Fauzi, Muhamad Saiful Nizam (2015)
Cinnamyl alcohol dehydrogenase (CAD) catalyses the committed step of monolignol biosynthetic pathway. Monolignols are monomers required in lignin synthesis. In plants, lignin is important for structural architecture and defence against pathogen attack. The CAD enzyme is encoded by a small multi-gene family whose members often differ in expression pattern. In oil palm, two copies of the CAD gene namely EgCAD1 and EgCAD2 have been identified and were equally expressed during oil palm development. Being a monocot with a relatively long life cycle, oil palm presents a great technical challenge for functional analysis of the gene in its native genome. Therefore, in this study, tobacco was chosen as a model plant to transform one of the CAD genes namely EgCAD2. In addition, the phylogeny of the CAD gene family from selected woody angiosperms was also constructed. Tobacco plants were transformed with two plasmids (pRI201-CAD2 and pMDC32-H2) based on the standard agrobacterium-mediated transformation protocol using leaf discs as target tissues. Antibiotic screening and PCR analysis of the transformed plants suggested that the transformation protocol was successfully implemented. Fifty-eight putative transformed plants were obtained based on the amplified EgCAD2 region of the transformation construct. The transformed plants exhibited normal phenotypes of wild tobacco plants based on the development of major organs at vegetative and reproductive stages. Phylogenetically, the CAD gene family was classified into four major groups with the oil palm CAD2 gene clustered together with members of group II. The gene shares the most recent common ancestor with Eucalyptus grandis, Theobroma cocoa, Malus domestica, Citrus cinensis and Populus trichocarpa. As a conclusion, the EgCAD2 gene was successfully integrated into the tobacco genome without interrupting functionally genes involved in normal plant development. The transformed plants would serve as important biological materials for functional characterisation of the oil palm CAD2 gene especially on its over-expressed effects on lignin deposition.